Genetics of preparation and response control in ADHD: the role of DRD4 and DAT1. (13th February 2014) - Albrecht, Björn; Brandeis, Daniel; von Sandersleben, Henrik Uebel‐; Valko, Lilian; Heinrich, Hartmut; Xu, Xiaohui; Drechsler, Renate; Heise, Alexander; Kuntsi, Jonna; Müller, Ueli C.; Asherson, Philip; Steinhausen, Hans‐Christoph; et al.
<x xml:space="preserve">Abstract</x> Background Difficulties with performance and brain activity related to attentional orienting (Cue‐P3), cognitive or response preparation (Cue‐CNV) and inhibitory response control (Nogo‐P3) during tasks tapping executive functions are familial in ADHD and may represent endophenotypes. The aim of this study was to clarify the impact of dopamine receptor D4 (DRD4) and dopamine transporter (DAT1) gene polymorphisms on these processes in ADHD and control children. Methods Behavioural and electrophysiological parameters from cued continuous performance tests with low and high attentional load were assessed in boys with ADHD combined type (N = 94) and controls without family history of ADHD (N = 31). Both groups were split for the presence of at least one DRD4 7‐repeat allele and the DAT1 10‐6 haplotype. Results Children with ADHD showed diminished performance and lower Cue‐P3, CNV and Nogo‐P3 amplitudes. Children with DRD4 7R showed similar performance problems and lower Cue‐P3 and CNV, but Nogo‐P3 was not reduced. Children with the DAT1 10‐6 haplotype had no difficulties with performance or Cue‐P3 and CNV, but contrary to expectations increased Nogo‐P3. There were no Genotype by ADHD interactions. Conclusions This study detected specific effects of DRD4 7R on performance and brain activity related to attentional orienting and response preparation, while DAT1 10‐6 was associated with elevated brain activity related to inhibitory response control, which potentially compensates increased impulsivity. As these genotype effects were additive to the impact of ADHD, the current results indicate that DRD4 and DAT1 polymorphisms are functionally relevant risk factors for ADHD and presumably other disorders sharing these endophenotypes.